2012
DOI: 10.1007/s00253-011-3843-9
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Corynebacterium glutamicum for the production of pyruvate

Abstract: A Corynebacterium glutamicum strain with inactivated pyruvate dehydrogenase complex and a deletion of the gene encoding the pyruvate:quinone oxidoreductase produces about 19 mM L: -valine, 28 mM L: -alanine and about 55 mM pyruvate from 150 mM glucose. Based on this double mutant C. glutamicum △aceE △pqo, we engineered C. glutamicum for efficient production of pyruvate from glucose by additional deletion of the ldhA gene encoding NAD(+)-dependent L: -lactate dehydrogenase (LdhA) and introduction of a attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 59 publications
2
71
0
4
Order By: Relevance
“…Consistent with previous reports, synthesis of lactate was greatly reduced from 0.85 to 0.05% by the deletion of ldh (Wieschalka et al, 2012). Moreover, the deletion of ldh was not the limiting step in the metabolic flow, since the growth rate and the Lleucine concentration of the ldh deletion strains were higher than the control.…”
Section: Effect Of Gene Deletions On Cell Growth and L-leucine Producsupporting
confidence: 91%
“…Consistent with previous reports, synthesis of lactate was greatly reduced from 0.85 to 0.05% by the deletion of ldh (Wieschalka et al, 2012). Moreover, the deletion of ldh was not the limiting step in the metabolic flow, since the growth rate and the Lleucine concentration of the ldh deletion strains were higher than the control.…”
Section: Effect Of Gene Deletions On Cell Growth and L-leucine Producsupporting
confidence: 91%
“…These approaches included (i) inactivating enzymes of D-pantothenate synthesis to limit CoA availability for the PDHC reaction (22,30,46), (ii) applying anaerobic conditions to abolish/reduce oxidative tricarboxylic acid (TCA) flux (47-49), (iii) using an ATPase-defective mutant leading to increased pyruvate availability (50,51), and (iv) deleting the aceE gene, encoding the E1p subunit of the PDHC (11,15,16,(25)(26)(27)(28). However, all these approaches either resulted TABLE 3 Substrate-specific biomass yield (Y X/S ), final titer, substrate-specific L-lysine yield (Y P/S ), and biomass-specific production rate (q P ) of C. glutamicum L-lysine producers cultivated in CGXII medium with 4% (wt/vol) glucose and 0.5% (wt/vol) BHI in shake flasks (DM1800) or in bioreactors (DM1933) in a requirement for D-pantothenate, ethanol, or acetate, did not allow an adequate adjustment of the PDHC activity and the carbon flux into the TCA cycle, and/or required a cleverly devised redox state of the cell (under anaerobic conditions).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also showed the successful employment of C. glutamicum for the production of the diamines putrescine and cadaverine (5)(6)(7)(8)(9)(10), the organic acids D-lactate, succinate, 2-ketoisovalerate, and pyruvate (11)(12)(13)(14)(15), the biofuels ethanol and isobutanol (16)(17)(18), xylitol (19), and heterologous proteins (20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study examined the additional deletion of pyruvate oxidase (pqo, or poxB gene) which improved L-valine production and also introduced an acetate growth requirement, suggesting that in C. glutamicum the combination of pyruvate oxidase, acetate kinase and phosphotransacetylase can bypass pyruvate dehydrogenase to allow acetyl CoA generation [72]. Further knockouts in the genes for lactate dehydrogenase (ldhA), two transaminases (alaT and avtA), and the replacement of native acetohydroxyacid synthase with an attenuated variant (C-T ilvN) led to 46 g/L pyruvate from glucose and acetate in 105 h at a yield of 0.48 g/g [73]. It should be noted that C. glutamicum and various yeasts including S. cerevisiae and C. glabrata have an active pyruvate carboxylase whereas E. coli do not.…”
Section: Metabolic Engineering Of Pathwaysmentioning
confidence: 99%